2021
DOI: 10.3390/jcm11010095
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Comorbidities, and Prescription Patterns of Korean Prurigo Nodularis Patients: A Multi-Institution Study

Abstract: Prurigo nodularis (PN) is a chronic dermatosis typified by extraordinarily itchy nodules. However, little is known of the nature and extent of PN in Asian people. This study aimed to describe the epidemiology, comorbidities, and prescription pattern of PN in Koreans based on a large dermatology outpatient cohort. Patients with PN were identified from the Catholic Medical Center (CMC) clinical data warehouse. Anonymized data on age, sex, diagnostic codes, prescriptions, visitation dates, and other relevant para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 27 publications
(45 reference statements)
4
40
0
Order By: Relevance
“…The long duration of the disease in these patients (median 36 months) may also contribute to accumulated prevalence of OCS and cyclosporine use. Medication use in the current study was generally similar to that reported in Korean and European studies, where TCS and antihistamines were the major medications, and where there was OCS use of >20% 26,27 . Taken together with our present study, there is a worldwide, unmet medical need for novel effective therapies in patients with severe PN.…”
Section: Discussionsupporting
confidence: 88%
“…The long duration of the disease in these patients (median 36 months) may also contribute to accumulated prevalence of OCS and cyclosporine use. Medication use in the current study was generally similar to that reported in Korean and European studies, where TCS and antihistamines were the major medications, and where there was OCS use of >20% 26,27 . Taken together with our present study, there is a worldwide, unmet medical need for novel effective therapies in patients with severe PN.…”
Section: Discussionsupporting
confidence: 88%
“…29 A Korean study found that prurigo nodularis was associated with chronic kidney disease (adjusted odds ratio 1Á48), dyslipidemia (1Á88), type 2 diabetes mellitus (1Á37), arterial hypertension (1Á50), autoimmune thyroiditis (2Á43), non-Hodgkin lymphoma (1Á95) and atopic dermatitis (2Á16). 30 Higher frequency and higher severity were shown in African Americans by comparison with other parts of the US population. 31 There is obviously no relationship with Fitzpatrick phototypes nor skin pigmentation.…”
Section: Epidemiologymentioning
confidence: 92%
“…A study of 223 patients from Finland also found frequent cardiovascular, respiratory, psychiatric or endocrine comorbidities 29 . A Korean study found that prurigo nodularis was associated with chronic kidney disease (adjusted odds ratio 1·48), dyslipidemia (1·88), type 2 diabetes mellitus (1·37), arterial hypertension (1·50), autoimmune thyroiditis (2·43), non‐Hodgkin lymphoma (1·95) and atopic dermatitis (2·16) 30 …”
Section: Epidemiologymentioning
confidence: 99%
“…74,75 Prurigo nodularis, another inflammatory dermatosis, is also associated with type 2 diabetes (adjusted odds ratio 1.37; 95% CI 1.22-1.54). 76 A link between atopic dermatitis and type 2 diabetes has also been demonstrated, with an odds ratio of 1.52 (95% CI 1.16-1.99) although some studies showed reduced odds of type 2 diabetes in patients with atopic dermatitis (odds ratio 0.78; 95% CI 0.71-0.84). 77,78 The reduced odds ratio in some patients with atopic dermatitis could be because those patients had already received anti-inflammatory treatment.…”
Section: Link Between Cutaneous Inflammation and Type 2 Diabetesmentioning
confidence: 99%
“…Epidemiological studies show that the risk of type 2 diabetes in subjects with psoriasis is higher than those without psoriasis (age‐adjusted relative risk 1.21, 95% confidence interval [CI] 1.01–1.44; body mass adjusted relative risk 1.64, 95% CI 1.23–2.18) 74,75 . Prurigo nodularis, another inflammatory dermatosis, is also associated with type 2 diabetes (adjusted odds ratio 1.37; 95% CI 1.22–1.54) 76 . A link between atopic dermatitis and type 2 diabetes has also been demonstrated, with an odds ratio of 1.52 (95% CI 1.16–1.99) although some studies showed reduced odds of type 2 diabetes in patients with atopic dermatitis (odds ratio 0.78; 95% CI 0.71–0.84) 77,78 .…”
Section: Consequences Of Altered Epidermal Functionsmentioning
confidence: 99%